Revisiting the Relationship of Poverty, Illiteracy, and Population Growth with Child Labour in Pakistan - Dr. Muhammad Hatim; Mubarka Abbas; Mahjabeen Arshad; Aniqa Aftab (Governance and Society Review, 2024)
The current study delved into the complex issue of child labour. The study aimed to extensively examine the interrelation between child labour, poverty, illiteracy, and population growth. As a matter of fact, child labour is still an existing issue in Pakistan, depriving children from their basic necessities, such as education and a safe childhood. The study used a random sampling technique to collect data from a broad sample of 384 respondents mainly from general public of Lahore. Data was collected using standardized questionnaire which was then rigorously analyzed using SPSS. The results revealed that there is a significant link between child labour and the factors of poverty, illiteracy, and the growth of population.The results contribute significantly to the existing body of research and provide valuable insights for policymakers